2007
DOI: 10.1016/j.jchromb.2007.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteomics of pancreatic cancer patients by multi-dimensional liquid chromatography and two-dimensional difference gel electrophoresis (2D-DIGE): Up-regulation of leucine-rich alpha-2-glycoprotein in pancreatic cancer

Abstract: We investigated the aberrant expression of plasma proteins in patients with pancreatic cancer. High-abundance plasma proteins (albumin, transferrin, haptoglobin, alpha-1-antitrypsin, IgG and IgA) were depleted by use of an immuno-affinity column, and low-abundance ones were separated into five fractions by anion-exchange chromatography. The fractionated plasma proteins were subjected to 2D-DIGE with highly sensitive fluorescent dyes. The quantitative protein expression profiles obtained by 2D-DIGE were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 42 publications
5
59
0
Order By: Relevance
“…Increased GDF15 mRNA and protein levels have been shown previously in pancreatic cancer tissue in comparison to adjacent normal controls (66) and evaluation of this protein in serum has also shown it to have diagnostic potential (67). Similarly, neutrophil gelatinase-associated lipocalin (LCN2) (71), matrix metalloproteinase 7 (MMP7) (68), complement component 3 (C3) (63,70), and leucine-rich alpha-2-glycoprotein (LRG1) (97) have been reported to be elevated in serum of pancreatic cancer patients, whereas mesothelin (MSLN) (98), tissue-type plasminogen activator (PLAT) (99), C-X-C motif chemokine 5 (CXCL5) (100) and other proteins highlighted in Table III have been shown to be up-regulated in pancreatic cancer or pancreatic neoplasia at the level of tissue and/or mRNA. In addition, other proteins, such as Lysyl oxidase-like 2 (LOXL2), have been associated with pancreatic cancer pathology and tumorigenicity.…”
Section: Discussionmentioning
confidence: 92%
“…Increased GDF15 mRNA and protein levels have been shown previously in pancreatic cancer tissue in comparison to adjacent normal controls (66) and evaluation of this protein in serum has also shown it to have diagnostic potential (67). Similarly, neutrophil gelatinase-associated lipocalin (LCN2) (71), matrix metalloproteinase 7 (MMP7) (68), complement component 3 (C3) (63,70), and leucine-rich alpha-2-glycoprotein (LRG1) (97) have been reported to be elevated in serum of pancreatic cancer patients, whereas mesothelin (MSLN) (98), tissue-type plasminogen activator (PLAT) (99), C-X-C motif chemokine 5 (CXCL5) (100) and other proteins highlighted in Table III have been shown to be up-regulated in pancreatic cancer or pancreatic neoplasia at the level of tissue and/or mRNA. In addition, other proteins, such as Lysyl oxidase-like 2 (LOXL2), have been associated with pancreatic cancer pathology and tumorigenicity.…”
Section: Discussionmentioning
confidence: 92%
“…Previous research has shown that LRG1 is involved in important pathological and biological processes, such as cell adhesion, signal transduction, and protein-protein interactions [21]. Recently, LRG1 was found to be elevated in the serum of patients with lung cancer, liver cancer, and pancreatic adenocarcinoma [22,23]. In the present study, it was found that LRG1 was up-regulated in CAA serum exosomes, suggesting that it may be involved in the development of CAA, and that the immune response to infection might contribute to the formation of CAA in KD.…”
Section: Discussionmentioning
confidence: 99%
“…A role for LRG1 has been suggested in promoting angiogenesis through activation of the TGF-b pathway (40). Apart from PDAC, increased LRG1 plasma levels have also been found in other cancer types (41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%